Online nursing education : a collaborative approach - Robinson, Melissa; Breen, Henny (Burlington, MA : Jones & Bartlett Learning, 2022)
'The increase of online nursing education programs has furthered the need for nursing faculty to have specific preparation for online teaching. Drawing from the authors' extensive experience teaching online nursing education programs, Online Nursing Education: A Collaborative Approach is unlike any other text. It was written and designed for faculty teaching online post-licensure students in a nursing education degree program, post-master's certificate program, advanced practice program, or other advanced education-related degree program. This unique text takes a theoretical approach and includes practical examples as well as sample curriculum, course design, and policies. Topics covered include strategies for teaching online, learning through writing in an online classroom, experiential learning in online programs, generational differences in online learning, and more practical discussions backed by evaluation studies and qualitative research'--Publisher's description.
Collaborative model for online nursing education -- Philosophical & theoretical approaches to online education -- Online nursing students -- Successful academic progression and online nursing students -- Quality assurance in online nursing programs -- Curriculum planning -- Online course design -- Online teaching strategies -- Learning through writing online classrooms -- Experiential learning in online nursing programs + appendix -- Narrative pedagogy -- Faculty role in academia -- The influence of generational differences on learning in the online classroom, research exemplar (PDF) (based on the PDF material) -- Assessing online collaborative discourse (PDF article by Henny Breen) -- Service learning enhances conceptual learning in a RN to BSN program (PDF article by authors).
Includes bibliographical references and index.
Description based on online resource; title from electronic title page (R2 Digital Library, viewed on December 1, 2020).
Master record variable field(s) change: 650
Keywords: Nursing -- Study and teaching; Internet in education; Computer-assisted instruction; Education, Nursing -- methods; Education, Distance -- methods; Interdisciplinary Placement -- methods; Curriculum -- standards; Students, Nursing; Distance education; Nursing -- Study and teaching; Electronic books; Electronic books